In Situ Fenestration: A Simple Technique for Fenestration of Acellular Dermal Matrix During Breast Reconstruction - Duek, Ori; Ben Naftali, Yeela; Pikkel, Yoav; Shoufani, Aziz (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Acellular Dermal Matrices (ADMs) were first described for use in breast surgery in 2001, and in 2005 it was first described to be used in breast reconstruction. However, ADMs are also associated with increased postoperative complications. Fenestration of the ADM may reduce the incidence of postoperative complications.Methods: We fenestrate the ADM in-situ, after attaching it to the lower pole of the planned pocket using absorbable sutures.Conclusions: using this technique enables to achieve a fan-shaped ADM mesh within less than a minute; Demonstrating a fast, easy and most importantly sterile method to fenestrate the ADM